FgMsn2 negatively regulates general stress responses and autophagy in Fusarium graminearum - Gu, Rongcheng; Jian, Yunqing; Liu, Zunyong (Phytopathology Research, 2025)
Effective adaptation to diverse stressors is essential for fungal survival and pathogenicity. The mechanisms underlying general stress responses in Fusarium graminearum , the pathogen responsible for Fusarium head blight (FHB) in cereal crops, remain unclear. In this study, we identify FgMsn2 as a negative regulator of general stress responses in F. graminearum . Deletion of FgMsn2 leads to resistance of F. graminearum to oxidative, osmotic, and cell wall stresses. Mechanically, FgMsn2 represses autophagy by inhibiting the expression of autophagy-related genes, including FgATG8 , and stress conditions trigger the cytoplasmic localization of FgMsn2. Additionally, the Δ FgMsn2 mutants show significantly reduced virulence on wheat, indicating the critical role of FgMsn2 in pathogenicity. These findings uncover a unique regulatory function of FgMsn2, which contrasts with its positive role in stress responses reported in other fungi, and provide valuable insights for developing novel strategies to manage FHB.